TANTANGAN DAN STRATEGI KOPERASI DALAM MENGHADAPI ERA DIGITAL PERSPEKTIF TATA KELOLA DAN AKUNTANSI FORENSIK - Faizul Idris; Siti Humulhaer; Gatot Subroto; Andriyani Susilawati; Ashuri (Berajah Journal, 2026)
This study aims to analyze the challenges and strategies of cooperatives in facing the digital era from the perspectives of governance and forensic accounting. The method used is a Systematic Literature Review (SLR) by examining various scientific sources, including journals, books, and official reports relevant to the research topic. The data were analyzed systematically to identify patterns, empirical findings, and research gaps related to digital transformation, good cooperative governance, internal control systems, and the application of forensic accounting in cooperatives. The findings indicate that the success of cooperative digital transformation is strongly influenced by the implementation of good governance principles, the strengthening of technology-based internal control systems, and the integration of forensic accounting approaches within supervisory mechanisms. The application of investigative auditing, digital data analysis, and continuous auditing systems has proven effective in enhancing the prevention and detection of fraud. The integration of sound governance practices, digital technology, and forensic accounting creates a model of digital cooperative management that is transparent, accountable, and sustainable. This study is expected to serve as a reference for cooperative managers and policymakers in formulating strategies for cooperative development in the digital era.